Assessing the influence of PM2.5 and PM10 on subjective thermal comfort in university classrooms - Hadjira SAKHRI (Journal of Air Pollution and Health, 2025)
Introduction: Indoor air quality plays a significant role in students' health and productivity. The present study attempts to examine the impact of air pollution on subjective thermal comfort and explores how the interaction between thermal conditions and Particulate Matter (PM) affects students' thermal comfort and health. Materials and methods: The data were collected through objective and subjective methods. The objective method consists the measurement of air pollution and meteorological parameters using the particle counter PCE-MPC 20. At the same time, subjective questionnaires were developed to obtain data relative to the students' sensations, preferences, and indoor environment during two periods of student occupancy and under two conditions: one with closed windows and one with natural ventilation. Results: Findings show that the average indoor and outdoor PM concentrations exceed the World Health Organization (WHO) standard. These suggest that universities would benefit from upgrading their heating systems and providing humidifiers. Results also highlight the difference between Predicted Mean Vote (PMV) and Thermal comfort; Thermal Sensation Vote (TSV), Thermal Preference Vote (TPV) and the need for adopted strategies in the perceived thermal comfort assessments. Additionally, the static results indicated the significant impact of PM on both TSV and TPV (P values<0.05) regardless of whether the windows are open or closed. Conclusion: To our knowledge, this is the first study conducted in Algeria to evaluate the effects of air pollution on students' perceived thermal comfort. The results underline the importance of addressing indoor air quality and prioritising natural ventilation strategies to enhance both student well-being and academic performance